Potential use of [gammadelta] T cell-based vaccines in cancer immunotherapy - Khan, Mohd Wajid A.; Eberl, Matthias; Moser, Bernhard (Frontiers in Immunology, 2014)
Immunotherapy is a fast advancing methodology involving one of two approaches: (1) compounds targeting immune checkpoints and (2) cellular immunomodulators. The latter approach is still largely experimental and features in vitro generated, live immune effector cells, or antigen-presenting cells. γδ T cells are known for their efficient in vitro tumor killing activities. Consequently, many laboratories worldwide are currently testing the tumor killing function of γδ T cells in clinical trials. Reported benefits are modest; however, these studies have demonstrated that large γδ T-cell infusions were well tolerated. Here, we discuss the potential of using human γδ T cells not as effector cells but as a novel cellular vaccine for treatment of cancer patients. Antigen-presenting γδ T cells do not require to home to tumor tissues but, instead, need to interact with endogenous, tumor-specific αβ T cells in secondary lymphoid tissues. Newly mobilized effector αβ T cells are then thought to overcome the immune blockade by creating proinflammatory conditions fit for effector T-cell homing to and killing of tumor cells. Immunotherapy may include tumor antigen-loaded γδ T cells alone or in combination with immune checkpoint inhibitors.